Một số dẫn liệu về mực nước biển trong Pleistocen muộn - Holocen vùng Hạ Long và Ninh Bình - Lâm, Doãn Đình; Boyd, W. E. (Vietnam Journal of Earth Sciences, 2001)
Some facts of sea-level fluctuation during the Late Pleistocene-Holocene in HaLong Bay and Ninh Binh area